Comparative Evaluation of Apical Extrusion Debris and Irrigant During Calcium Hydroxide Removal and Endodontic Instrumentation Using Three Types of Instrumentation Systems - Saricam, Esma; İnce Yusufoğlu, Selen (Journal of Dentistry Indonesia, 2020)
Many root canal preparation techniques and instruments produce apically extruded materials to a certain extent depending on the preparation system adopted. The extrusion of debris from the apical foramen during chemomechanical preparation may cause postoperative pain and failure of endodontic treatment. Objective: This study evaluates the differences in the apical extrusion of debris and calcium hydroxide (CH) during endodontic instrumentation by using Reciproc Blue (RB), WaveOne Gold (WOG), and F6 Skytaper (F6). Methods: Six experimental study groups (n = 13) were established. The root canal procedures for all groups were prepared with different methods: Group I: One Shape (OS) instrumentation, CH filling for 21 days, removal of CH using RB; Group II: OS instrumentation, CH filling for 21 days, removal of CH using WOG; Group III: OS, CaOH filling for 21 days, removal of CH using F6; Group IV: root canal instrumentation using RB; Group V: root canal instrumentation using WOG; Group VI: root canal instrumentation using F6. Apically extruded debris was collected into preweighed Eppendorf tubes by using the Myers and Montgomery method. Data were statistically analyzed with one-way ANOVA and Kruskal–Wallis tests. Results: All the tested instruments caused the extrusion of debris and irrigant from the apical foramen. The difference among the six groups was not statistically significant (p > 0.05). Conclusions: The tested instruments caused similar apical extrusions of debris and irrigant during CH removal or instrumentation procedures.